Verify that `y= -t*cos t - t` is a solution of the initial-value problem `t*(dy/dt)=y+(t^2)sint` and `y(pi) = 0`
- print Print
- list Cite
Expert Answers
Tushar Chandra
| Certified Educator
calendarEducator since 2010
write12,545 answers
starTop subjects are Math, Science, and Business
Given that `y = -t*cos(t)-t`
`dy/dt = -t*(-sin t) - cos t - 1`
= `t*sin t - cos t - 1` ...(1)
`y/t + t*sin t `
=...
(The entire section contains 81 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- Verify that `y = -tcos(t) - t` is a solution of the initial value problem `t(dy/dt) = y +...
- 1 Educator Answer
- `x=e^(-t)cost , y=e^(-t)sint , 0<=t<=pi/2` Find the arc length of the curve on the...
- 1 Educator Answer
- `f(t) = e^sin(t) cos(t), [0, pi/2]` Find the average value of the function on the given...
- 1 Educator Answer
- Assume that x and y are both differentiable functions of t and find the required values of dy/dt...
- 1 Educator Answer
- Solve the initial value problem: `dy/dt = sint+1` , `y(pi/3) = 1/2` I do not know how to do it at...
- 1 Educator Answer